Antioxidant Profile of Commonly Consumed Fruits And Vegetables in India (Bangladesh Journal of Botany, 2022)
Vitamin C, β carotene and phenolics constitute the major class of antioxidants in fruits and vegetables which protect cell against oxidative damage and prevent humans from degenerative diseases. Antioxidants profile in terms of content and capacity in each 10 commonly consumed fruits and green leafy vegetables (GLV) using phenolics, flavonoids, FRAP, DPPH radical scavenging activity, vitamin C and β carotene analysis were determined. Among fruits aonla had the highest total phenolics (1654 mg GAE/100 g), total flavonoids (512.49 mgRE/100 g), FRAP (23055 mgTE/100 g), DPPH radical scavenging activity (6322.36 mgRE/100 g) and vitamin C (401 mg/100g) followed by grapes, Ziziphus and guava. Mango contained exceptionally high (2210.99 μg/100 g) amount of β- carotene whereas papaya contained 630.48 μg/100 g. Among GLVs mint leaves, curry leaves and Chinopodium leaves had been an excellent source of antioxidants. Regular consumption of GLVs and fruits can protect from degenerative diseases and aging and may provide longevity.Bangladesh J. Bot. 51(1): 45-50, 2022 (March)